2016
DOI: 10.2147/ott.s119428
|View full text |Cite
|
Sign up to set email alerts
|

BRAF inhibitors and radiotherapy for melanoma brain metastases: potential advantages and disadvantages of combination therapy

Abstract: Melanoma is an aggressive malignancy that frequently spreads to the brain, resulting in rapid deterioration in both quality and quantity of life. Historically, treatment options for melanoma brain metastases (MBM) have predominantly consisted of surgery and radiotherapy. While these options can help provide local control, the majority of patients still develop intracranial progression. Indeed, novel therapeutic options, including molecularly targeted agents and immunotherapy, have improved outcomes and are now… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 67 publications
3
26
0
Order By: Relevance
“…Many clinical trials were addressed to B-Raf pathway inhibition. A phase 2 clinical trial performed between 2011 and 2015 on 146 patients using an inhibitor of B-Raf pathway (vemurafenib) has showed that vemurafenib is an efficient drug for BM with B-raf mutation but not all BM are vemurafenib sensitive (46,47). Therefore, other clinical trials were designed to combine multiple pathway inhibitors or to combine surgical and systemic therapy (e.g., immunotherapy).…”
Section: Translational and Clinical Studies Targeting Bm Specific Molmentioning
confidence: 99%
“…Many clinical trials were addressed to B-Raf pathway inhibition. A phase 2 clinical trial performed between 2011 and 2015 on 146 patients using an inhibitor of B-Raf pathway (vemurafenib) has showed that vemurafenib is an efficient drug for BM with B-raf mutation but not all BM are vemurafenib sensitive (46,47). Therefore, other clinical trials were designed to combine multiple pathway inhibitors or to combine surgical and systemic therapy (e.g., immunotherapy).…”
Section: Translational and Clinical Studies Targeting Bm Specific Molmentioning
confidence: 99%
“…Following lung and breast cancer, melanoma is the third most common reason for brain metastases (4). Melanoma spreads to the brain in ≤75% of patients with melanoma (5). Brain metastases cause mortality in 95% of patients with high class (Class III) (6).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of BM is steadily increasing, in part due to increased surveillance and improvements in systemic extracranial therapy [2, 3]. The standard of care for BM continues to evolve given advancements in focal therapies, including stereotactic radiosurgery (SRS), which can offer a high rate of local control without the consequences of whole brain radiotherapy (WBRT) [4].…”
Section: Introductionmentioning
confidence: 99%